Trace‐element XAFS sensitivity: a stress test for a new XRF multi‐detector. (18th October 2021) - Carlomagno, Ilaria; Antonelli, Matias; Aquilanti, Giuliana; Bellutti, Pierluigi; Bertuccio, Giuseppe; Borghi, Giacomo; Cautero, Giuseppe; Cirrincione, Daniela; de Giudici, Giovanni; Ficorella, Francesco; Gandola, Massimo; Giuressi, Dario; et al.
Abstract : A new multielement X‐ray fluorescence detector is presented, specifically designed to probe the chemical speciation of trace 3 d elements down to the p.p.m. range. Abstract : X‐ray absorption fine‐structure (XAFS) spectroscopy can assess the chemical speciation of the elements providing their coordination and oxidation state, information generally hidden to other techniques. In the case of trace elements, achieving a good quality XAFS signal poses several challenges, as it requires high photon flux, counting statistics and detector linearity. Here, a new multi‐element X‐ray fluorescence detector is presented, specifically designed to probe the chemical speciation of trace 3 d elements down to the p.p.m. range. The potentialities of the detector are presented through a case study: the speciation of ultra‐diluted elements (Fe, Mn and Cr) in geological rocks from a calcareous formation related to the dispersal processes from Ontong (Java) volcanism (mid‐Cretaceous). Trace‐elements speciation is crucial in evaluating the impact of geogenic and anthropogenic harmful metals on the environment, and to evaluate the risks to human health and ecosystems. These results show that the new detector is suitable for collecting spectra of 3 d elements in trace amounts in a calcareous matrix. The data quality is high enough that quantitative data analysis could be performed to determine their chemical speciation.